PENGARUH KESADARAN WAJIB PAJAK TERHADAP PENINGKATAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR PADA UNIT PELAKSANA TEKNIS PELAYANAN PENDAPATAN DAERAH PONTIANAK WILAYAH I SAMSAT SIANTAN - CORNELUS, CORNELUS; Yohanes, Yulius; Hanum, Aliyah Nuraini (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aims to reveal how much the voluntary tax compliance affects the partial increase in motor vehicle tax payments. The phenomenon that occurs in this study is whether the increase in motor vehicles every year is followed by an increase in motor vehicle tax revenue. The results of this study show that voluntary tax compliance had no partial effect on the increase in motor vehicle tax payments with a value of t-calc = 1.576 and significance = 0.119. This type of research used a quantitative method with a descriptive approach. According to Sugiyono (2016: 15), "The quantitative method is data that is expressed in the form of numbers or qualitative data which are described in numbers.". This study used a descriptive approach with the aim of describing the object of research or results of research.Keywords: Voluntary Tax Compliance and Increased Motor Vehicle Tax PaymentsÂ